Proceso administrativo de la empresa “Corporacion Agrotecnologia EC" - Barahona Tutillo, Nadia Mishell (2023)
The research project seeks to analyze the administrative process in the company AgroTech Corp knowing the current situation of the company and thus determine if it contributes to the efficiency of operations within the company, the reviewed information will serve as a guideline that allows to know more about the administrative process and the different points of view of different authors, in addition the present problem is known and a proposal is determined which favors the improvement of efficiency in the production area of the company, after carrying out the analysis it was established that the Lack of training has been a factor that has generated a serious dispute among company personnel since many are unaware of the business philosophy and therefore do not clearly know the business objectives, therefore it was important to propose a training plan where publicize the structure of the company, issues about decision making and assertive communication, therefore it seeks to strengthen the efficiency of operations through the solution to the problems observed and thus help both its manager and its collaborators to maintain a better work environment.